Micro-teaching as a tool: Identifying factors influencing English additional language speaking pre-service teachers’ English instruction and learning interactions - Meyers, Rozanne (Journal for Language Teaching, 2025)
Many South African teachers are required to competently and confidently use English as a tool for learning interaction with their learners and as a medium of instruction. This might be problematic for English additional language pre-service teachers, whose medium of instruction is not English. This paper explores how micro-teaching can be used to identify factors that influence the abilities of English additional language speaking pre-service teachers to use English as a medium of instruction. Three data collection instruments were used in this case study: an observation checklist completed by the researcher during micro-teaching lessons; a questionnaire completed by each participant after they conducted their micro-teaching lesson; and an unstructured interview with each participant, which served as an opportunity for clarification and discussion on the data generated from the observation checklist and questionnaire. Data collection and analysis operated under an interpretivist framework, using a thematic approach to data analysis. Data generated from the three instruments supported the identification of factors that influence participants’ abilities to teach in English. Learner interaction and lesson preparation and execution emerged as the two main themes of the data analysis The findings of this study hold implications for English additional language pre-service teachers, Teaching Practice and Work Integrated Learning departments, didactic lecturers and the broader tertiary education sector.